Electrochemical Measurements on Palladium Cathodes in LiOD/D2O Solutions related to the «Cold Fusion Experiments» - Jan Augustynski; Martine Ulmann; Jiangbo Liu (CHIMIA)
The current-voltage behaviour of palladium electrodes, polarized in an electrolysis cell filled up with a diluted solution of lithium deuteroxide in heavy water, is shown to be strongly influenced by the impurities co-depositing at the cathode. Among the impurities, identified on the surface of palladium at the end of the electrolyses, lead and especially zinc cause the shift of the electrode potential making possible lithium deposition and lithium deuteride formation. Some expected interactions of these compounds are discussed.